ANALISIS PORTOFOLIO OPTIMAL MODEL CAPM DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA IDXQ30 - Gracia Nazaretha Nauli br Silitonga; Alfida Aziz (STIE Mahardhika, 2023)
This paper aimed to analyze the optimal portfolio based on the Capital Asset Pricing Model (CAPM) method by classifying the undervalued and overvalued stocks. The population of this paper are stocks listed on IDXQ30 in the 2022-2023 period, there are 22 stocks used as research samples. This paper used IDXQ30 daily closing price, closing price of the daily Jakarta Stock Exchange Composite Index on the IDX, and Bank Indonesia's daily reference interest rate or the BI-7 Day Reverse Repo Rate. The results of this paper indicated that CAPM method generates 8 undervalued stocks and 14 overvalued stocks. Undervalued stocks consist of KLBF, ITMG, ASII, UNTR, BBCA, PTBA, BMRI and HRUM while overvalued stocks consist of MIKA, SIDO, HEAL, INTP, UNVR, HMSP, MNCN, CPIN, TLKM, TAPG, LSIP, ACES, SCMA and SRTG. The investment decisions are made by buying stocks that are classified as undervalued and selling stocks that are classified as overvalued. Keywords: Capital Asset Pricing Model, IDXQ30, Investment Decision, Optimal Portfolio